2021
DOI: 10.1093/tas/txab012
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the effect of glycerin inclusion in dairy cattle diet on milk fatty acid profile

Abstract: The use of glycerin in diets for dairy cows initially emerged as an alternative for the prevention and control of ketosis. However, despite some controversy, there are still several studies associating glycerin with increases in daily milk yield, with possible changes in its constituents. Therefore, the objective of this study was to evaluate, using a meta-analysis approach, the effect of glycerin inclusion in dairy cow diets on milk fatty acid. Twenty-two peer-reviewed publications with 66 treatment means wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
2
1
0
Order By: Relevance
“…The high concentration of glucose in T2 and T3 groups may be due to the fact that the dietary glycerol is mostly absorbed directly by the rumen epithelium or the small intestine and transported through the bloodstream to the liver where the enzyme glycerol kinase converts it to glycerol-3-phosphate used to stimulate glucose formation in the liver through the process of gluconeogenesis (31,41), or due to the fermentation of glycerol by rumen bacteria to propionate, which is transferred to the liver to convert to Succinyl-CoA, which enters the Krebs cycle to turn into pyruvate phosphoenol to form glucose through the process of Gluconeogenesis (35). This result is consistent with the study of Torres et al (45) who reported that glycerol increases blood glucose concentration by 2.5%, and also the study of Goff and Horst (21), who indicated that giving milk cows with an amount of 1, 2 or 3 liters of glycerol results in an increase in blood glucose by 16%, 20%, and 25%, respectively, as glycerol is one of the precursors that form glucose from the process of gluconeogenesis in the liver (21). In addition to other studies, which showed the positive effect of glycerol in increasing blood glucose concentration in dairy cows (11,46,47).…”
Section: Results and Discussion Milk Yield And Componentssupporting
confidence: 90%
See 2 more Smart Citations
“…The high concentration of glucose in T2 and T3 groups may be due to the fact that the dietary glycerol is mostly absorbed directly by the rumen epithelium or the small intestine and transported through the bloodstream to the liver where the enzyme glycerol kinase converts it to glycerol-3-phosphate used to stimulate glucose formation in the liver through the process of gluconeogenesis (31,41), or due to the fermentation of glycerol by rumen bacteria to propionate, which is transferred to the liver to convert to Succinyl-CoA, which enters the Krebs cycle to turn into pyruvate phosphoenol to form glucose through the process of Gluconeogenesis (35). This result is consistent with the study of Torres et al (45) who reported that glycerol increases blood glucose concentration by 2.5%, and also the study of Goff and Horst (21), who indicated that giving milk cows with an amount of 1, 2 or 3 liters of glycerol results in an increase in blood glucose by 16%, 20%, and 25%, respectively, as glycerol is one of the precursors that form glucose from the process of gluconeogenesis in the liver (21). In addition to other studies, which showed the positive effect of glycerol in increasing blood glucose concentration in dairy cows (11,46,47).…”
Section: Results and Discussion Milk Yield And Componentssupporting
confidence: 90%
“…This result is consistent with the study of Kupczynski et al (30), conducted on Holstein cows, by given 300 ml / day of pure glycerol, and the result was a decrease in the concentration of NEFA and BHBA and an increase in the serum concentration of triglycerides, indicating the positive effect of glycerol on reducing the level of NEFA and BHBA (47). Similarly, Torres et al (45) reported that glycerol increases the serum concentration of glucose in the blood by 2.5% and reduces the concentration of NEFA by 5.6%. REFERNCES…”
Section: Results and Discussion Milk Yield And Componentssupporting
confidence: 89%
See 1 more Smart Citation